A scalable synthesis route for multiscale defect engineering in the sustainable thermoelectric quaternary sulfide Cu26V2Sn6S32. (15th August 2020) - Guélou, Gabin; Couder, Christophe; Bourhim, Abdelhamid; Lebedev, Oleg I.; Daneu, Nina; Appert, Florian; Juraszek, Jean; Lemoine, Pierric; Segreto, Lorraine; Guilmeau, Emmanuel
Abstract: In recent years, thermoelectric materials inspired from the natural mineral colusite have emerged as a new class of environmentally-friendly copper-based sulfides composed of abundant elements. Herein, high performance bulk colusite Cu26 V2 Sn6 S32 materials were synthesized using mechanical alloying and spark plasma sintering of low-cost industrial-grade metal sulfides. This new synthesis route has led to the formation of various types of nano-to-microscale defects, from local Sn-site structural disorder to nano-inclusions and vanadium-rich core-shell microstructures. These multiscale defects have a strong impact over phonon scattering, making it possible to reach ultra-low lattice thermal conductivity. Simultaneously, the electrical transport properties are impacted through variations in charge carrier concentration and effective mass, leading to a synergistical improvement of both electrical and thermal properties. The resulting power factor, over 1 mW m −1 K −2 above 623 K with an average value of 0.86 mW m −1 K −2 over the temperature range 300 ≤  T / K  ≤ 650 K, is the highest reported for a germanium-free colusite to date. Our optimization strategy based on defect engineering in bulk materials is an exciting prospect for new low-cost thermoelectric systems. Graphical abstract: Image, graphical abstract